The Laboratory Guinea Pig (second edition) - Clemons, Donna J. (Taylor & Francis, 2018)
Praise for the First Edition "This book is easy to read and has many informative illustrations...I would strongly recommend this book to those interested in a broad introduction to the care and use of laboratory guinea pigs as well as to laboratory animal technicians, managers, veterinarians and scientists who do not have direct access to large, well organized animal resource units with extensive library facilities." -John D. Young, Contemporary Topics The Laboratory Guinea Pig provides a compact and well- illustrated introduction to research on the guinea pig. The second edition of this popular handbook facilitates quick reference to the behavioral and physical traits of the guinea pig, as well as practical information on its unique anatomical and biological features. Numerous tables and color illustrations help the reader identify features of anatomy and understand health issues and care requirements. Supplying a stepwise introduction to common laboratory techniques, the new edition of this trusted reference provides guidance that supports the humane care and use of guinea pigs in the laboratory setting.